Policy making : agenda-setting in the new media era in Singapore - Gabriel, Sim (2019)
The relationship between the government and the media ranges from a spectrum, with extreme ends aptly labelled as “watchdog” or “lapdog”. Singapore is a first-world country which has notably achieved high rates of growth and stability in a short period of time since its separation from Malaysia. Unlike most democracies, Singaporean mainstream media supports the key agendas of the government, resulting in significantly lower press freedom ratings. However, is there an agenda setting relationship between the media and the government? Can the media somehow influence the policy agenda? Who decides what makes new so prominent and salient that the hot topic must be brought up in parliament? This paper hypothesizes that there is an agenda setting process using the media to influence the policy agenda. Furthermore, mainstream media may give particular issues significant focus and attention until they are address by members of parliament. Case studies of the controversies surrounding Singapore’s Public Housing policy, anti-homosexual law, and the salaries of ministers will be used to answer these questions.